The Pricing Evaluation Using The Cost-Plus Pricing Method at CV Macarindo Berkah Group in Jember District - Tiara, Tiara; Maulidia, Yulinar; Kantun, Sri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2023)
This study aims to evaluate the determination of the selling price using the cost-plus pricing method on CV Macarindo Berkah Group with existing standards. This research is evaluative and the data collection method used in this study is a document. The data analysis method used in this study is evaluative analysis. The components assessed in this study are the completeness of cost classification based on the main function in the company, based on the relationship with something being financed, based on the relationship with the level of activity, and the completeness of the selling price stages using the cost-plus pricing method. Based on the 14 components evaluated, 9 components comply with the standard. Components that have not been carried out are the classification of costs based on their relationship to something being financed, the absence of ROI (Return Of Investment), cost classification, and income statement. The suitability level of setting the selling price using the cost-plus pricing method at CV Macarindo Berkah Group shows that it is following existing standards with a conformity level of 64.28%. The suitability of setting the selling price seen from the percentage results shows the criteria of "Appropriate". A discrepancy of 35.72% can be replaced with a similar function.